Curcumin encapsulation in nanostructures for cancer therapy: A 10-year overview - D'Angelo, Natália A.; Noronha, Mariana A.; Kurnik, Isabelle S. [UNESP]; Câmara, Mayra C.C.; Vieira, Jorge M.; Abrunhosa, Luís; Martins, Joana T.; Alves, Thais F.R.; Tundisi, Louise L.; Ataide, Janaína A.; Costa, Juliana S.R.; Jozala, Angela F.; et al. (Elsevier, 2021)
Curcumin (CUR) is a phenolic compound present in some herbs, including Curcuma longa Linn. (turmeric rhizome), with a high bioactive capacity and characteristic yellow color. It is mainly used as a spice, although it has been found that CUR has interesting pharmaceutical properties, acting as a natural antioxidant, anti-inflammatory, antimicrobial, and antitumoral agent. Nonetheless, CUR is a hydrophobic compound with low water solubility, poor chemical stability, and fast metabolism, limiting its use as a pharmacological compound. Smart drug delivery systems (DDS) have been used to overcome its low bioavailability and improve its stability. The current work overviews the literature from the past 10 years on the encapsulation of CUR in nanostructured systems, such as micelles, liposomes, niosomes, nanoemulsions, hydrogels, and nanocomplexes, emphasizing its use and ability in cancer therapy. The studies highlighted in this review have shown that these nanoformulations achieved higher solubility, improved tumor cytotoxicity, prolonged CUR release, and reduced side effects, among other interesting advantages.
Keywords: Bioactive encapsulation; Cancer therapy; Curcumin (CUR); Drug delivery systems (DDS); Nanostructures; Nanotechnology